The Relevance Of Improving Diagnostic And Therapeutic Measures For Viral Hepatitis - Zukhra Nuruzova Abdukadirovna (International Journal of Medical Sciences And Clinical Research, 2025)
This review aims to summarize the current evidence on the treatment of viral hepatitis, focusing on its clinical management. Also, future treatment options and areas of potential research interest are detailed. PubMed and Scopus databases were searched for primary studies published within the last ten years. Keywords included hepatitis A virus, hepatitis B virus (HBV), hepatitis C virus, hepatitis D virus (HDV), hepatitis E virus, and treatment. Outcomes reported in the studies were summarized, tabulated, and synthesized. Significant advances in viral hepatitis treatment were accomplished, such as the advent of curative therapies for hepatitis C and the development and improvement of hepatitis A, hepatitis B, and hepatitis E vaccination. Targeted antiviral medications against HBV (immunomodulatory therapies and gene silencing technologies) are potential ways to eradicate the virus, however there are currently no pharmaceuticals that cure hepatitis B beyond viral suppression. In the end, widespread test-and-treat initiatives with high screening rates and high immunization rates may eradicate viral hepatitis and lessen its impact on healthcare systems. Although more research is needed, the discovery of a cure for hepatitis C has rekindled interest in curing hepatitis B. Clinical research is now being conducted on novel therapy approaches that target the HDV life cycle. It is possible to avoid viral hepatitis A, B, and E infections with effective vaccinations. Over 90% of people with chronic hepatitis C can be cured with new oral, well-tolerated therapy regimens. People with chronic hepatitis B virus infection can also receive effective therapy; however, for the majority of patients, this treatment must be long-term, and more recent advancements hope to provide a "functional cure" for hepatitis B. The latest recent developments in viral hepatitis diagnosis and therapy are covered in this review article.